Expressive alignment with timbre: changes of sound-kinetic patterns during the break routine of an electronic dance music set - Marchiano, María (2018)
Background: Expressive alignment (Leman, 2016) refers to the synchronization of human movement patterns with musical patterns. On the one hand, Solberg and Jensenius (2017) found that dancers share a movement pattern during the break routine (BR) of electronic dance music (EDM) tracks (sound pattern formed by breakdown-build up-drop sequence which constitutes a formal articulation of EDM set). On the other hand, although a number of timbral dimensions have been established which organize auditory perception (Alluri, 2012), expressive alignment with timbral patterns have not been studied yet. In this work we studied the timbral relevance of the acoustic changes during BRs of EDM’s sets, and assume that these changes form musical patterns that, in turn, afford changes in human movement patterns. Aims: To describe the changes of sound-kinetic patterns during the BRs on an EDM party video, resulting from the expressive alignment between human movement patterns and sonic patterns of music. Methods: Stimulus: an EDM party audiovisual record. Sound analysis: (1) Aural identification, description and temporal location annotation on Elan 5.0 timeline of all the BRs of the EDM set. (2) Processing of its acoustic signal, and extraction of features related to timbre, rhythm and pitch with MIRToolbox. Movement analysis: (1) Detection of movement patterns formed by arms, head and shoulders of all people completely visible on the video during 15 BRs. (2) Laban Movement Analysis (Laban, 1950) video annotation on Elan 5.0 of effort-shape elements of each movement pattern. (3) Comparative analysis of the movement patterns of each person. Results: Sound analysis results show that the BR is defined by an acoustical pattern, in which some timbral features play a relevant role. With regard to movement analysis; (1) we identified changes on movement patterns during BRs, especially at the drop moment ; (2) we noted that people develop personal movement patterns, differentiated from those of others by the organization of effort-shape elements; and (3) changes in the dancers´ personal style of movement patterns occur at the same time. Conclusions: In this work we observed that EDM dancers develop expressive alignments during the BR. From a musical point of view, the changes in acoustical features related to timbre during the BR modify the sonic environmental conditions, and the consequent expressive alignment of the dancers. Although people keep their personal styles of movement, they all change their movement patterns in phase with the changes of music, producing a shared sound-kinetic pattern. References: Alluri, V. (2012). Acoustic, Neural, and Perceptual Correlates of Polyphonic Timbre (Doctoral Thesis). University of Jyväskylä: Jyväskylä. Laban, R. (1950). The Mastery of Movement. Binsted: Dance Books. Leman, M. (2016). The Expressive Moment. How Interaction (with Music) Shapes Human Empowerment. Massachusetts: MIT Press. Solberg, R.T. y Jensenius, A.R. (2017). Arm and head movements to musical passages of electronic dance music. Book of Abstracts, 25th ESCOM. Gent: ESCOM.